Are farmer organizations (FOs) such a big deal for agroecological innovation? An assessment of smallholders FOs’ innovation intermediation functioning - Ouerghemmi, Hassen; Frija, Aymen (International Center for Agricultural Research in the Dry Areas, 2024)
Intermediary actors play a crucial role in facilitating agroecological innovation transfer. Farmers' Organizations (FOs) act as knowledge and innovation intermediaries, supporting farmers in adopting agroecological practices over extended periods. FOs influence farmers' decisions to implement agroecological innovations by affecting their motivation and behavior. Agroecological innovation systems (AeISs) involve diverse actors and organizations, fostering collective intelligence and empowering stakeholders to adapt to complex challenges. This research addresses the role of FOs in Tunisia with a historical reflection on national policy related to collective action in agriculture. Then evaluating the potential roles of a sample of FOs in Agroecological transition.